Enzymatic deracemization of halogenated dihydroindenols and dihydroindenediols substituted in benzene ring - Prysiazhnuk, D.V.; Kolodiazhna, O.O.; Kolodiazhnyi, O.I. (Доповіді НАН України, 2020)
The optically active halodihydroindenols and dihydroindenediols are components of many biologically active natural compounds, being important pharmacophore groups. In the present work, to obtain the above compounds with a high degree of optical purity, the resolution of racemates into enantiomers using enzymes is proposed. Dihydroindenones, which were reduced with sodium borohydride to dihydroindenols, were used as starting compounds. Burkholderia cepacia lipase (BCL) was used to separate racemic indenols. Racemic indenols were kinetically trans-esterificated with vinyl acetate in organic media in the presence of a BCL biocatalyst. As a result, acylated indenols of (R)-ab solute configuration and unreacted indenol of (S)-configuration, which were separated into individual compounds by column chromatography, were obtained. The enzymatic resolution of halodihydrinindene acetates by hydrolysis in the presence of Candida antarctica B lipase immobilized on diatomite was also investigated. Enantiomerically enriched halodihydroindenols and halodihydrinindene acetates were obtained when racemic halodihydrinindene acetates were treated with Novozym 435® in MTBE for 20—30 hours at 30—40 °C. The enantiomeric purity of the compounds was determined by the derivatization with Mosher acid. The absolute configuration of the compounds was established by the Kazlauskas method.